The effect of combined antihypertensive therapy on left ventricular diastolic function in resting and postexercise patients with arterial hypertension - M. Yu. Kolesnyk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2015)
The correction of left ventricular diastolic function abnormalities hasn’t been well investigated in arterial hypertension.